2020
DOI: 10.24014/jupet.v17i1.8828
|View full text |Cite
|
Sign up to set email alerts
|

Kualitas Nutrisi Dan Fraksi Serat Wafer Ransum Komplit Dengan Penambahan Level Ampas Sagu Yang Berbeda Pada Sapi Bali

Abstract: Sago waste is the result of agricultural waste whose use as feed is still very limited even though the amount is quite large but sago waste has a high crude fiber content, and low protein content so that is needs further processing, one of which is processing become a wafer complete ration. The study used the Complete Randomized Design (CDR), method with 4 treatments and 4 replications, which consisted of P0: complete wafer ration + 0% sago waste, P1: complete wafer ration + 10% sago waste, P2: complete wafer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
1
0
Order By: Relevance
“…The use of plant protein sources in feed can make a big contribution for several reasons such as being cheap, easy to obtain, and available in the community. The CP content in this study was not much different from that reported by Mucra et al [27] on complete feed wafer substituted with corn bran and the sago meals which resulted in CP levels of 11.92%-13.92%. This is because these studies used similar materials but different sources of starch and adhesive.…”
Section: Discussioncontrasting
confidence: 74%
“…The use of plant protein sources in feed can make a big contribution for several reasons such as being cheap, easy to obtain, and available in the community. The CP content in this study was not much different from that reported by Mucra et al [27] on complete feed wafer substituted with corn bran and the sago meals which resulted in CP levels of 11.92%-13.92%. This is because these studies used similar materials but different sources of starch and adhesive.…”
Section: Discussioncontrasting
confidence: 74%
“…The disease frequently found is suffering from intestinal worms. Sadarman et al (2007) the worms in the body will disturb animal health and automatically affect production and reproduction. In Indonesia, the prevalence of suffering from intestinal worm is still relatively high, both among animals and humans, which suffer an economic loss and are harmful to animal health.…”
Section: Threats Of Cattle Farming Development In Sidomulyomentioning
confidence: 99%